A Study of Students’ Perception about Role of Technology in promoting Online Education during Covid-19 - Ghosia, Sana; Rashid, Sobia; Rasool, Shafqat (Annals of Human and Social Sciences, 2023)
The COVID-19 pandemic situation all over the world forced universities to close their campuses and educational activities were shifted to online platforms. In Pakistan Universities were partially ready for online shifts, and the students’ learning processes were sustained through different online platforms. The main purpose of this study was to identify the role of online platforms in facilitating students during pandemic. The present study was based on the opinions of BS and Master Students in Pakistan universities, and their points of view about various aspects of online classes were sought during the ongoing pandemic. 312 students responded to our survey. Students believed that the implementation of online classes simplified lectures, activities, discussions, and assignments. Students’ performance was assessed with online quizzes and tests. Students’ interest in learning grows as a result of the interactivity fostered by online classes. In conclusion, they discovered that online education will be advantageous in the future. Based on the findings of this study it is strongly recommended that online education and online learning should be continued in future as well.